Influence of Tantalum Addition on Microstructure and Mechanical Properties of the NiAl-Based Eutectic Alloy - Sheng, L.Y.; Du, B.N.; Lai, C.; Guo, J.T.; Xia, T.F. (Проблемы прочности, 2017)
NiAl-28Cr-6Mo or NiAl-Cr(Mo) eutectic alloys with different degree of tantalum (Ta) addition have been fabricated and investigated. The microstructural characterization shows that minor Ta addition results in the formation of Cr2Ta Laves phase with C14 crystal structure. Small Laves phases are prone to precipitation along Cr(Mo) phase boundary, while large/bulk ones are formed in the intercellular region. As compared with the NiAl-Cr(Mo) eutectic alloy, minor Ta addition can refine Cr(Mo) and NiAl eutectic lamella in the core of eutectic cell but coarsen the Cr(Mo) and NiAl phase in the fringe of eutectic cell. An increased Ta addition invokes coarsening of Cr(Mo) and NiAl phases in the intercellular region and enhances Laves phase precipitation in the intercellular region. When the Ta addition increases to 2.0 at.%, the modified alloy mainly comprises ultrafine eutectic cell core and coarse Cr(Mo) and NiAl phases, which are semi-separated by NiAl dendritic and bulk Laves phase. The results confirm that the appropriate Ta addition can significantly improve the high-temperature strength with a feeble effect on room-temperature ductility, which can be ascribed to the microstructure optimization induced by the Ta addition. However, further Ta addition strongly affects the cellular eutectic microstructure and is detrimental for the room-temperature ductility. The appropriate Ta content in the NiAl-Cr(Mo) eutectic alloy should be about 1.0 at.%.